An ecological model of adaptation to displacement: individual, cultural and community factors affecting psychosocial adjustment among Syrian refugees in Jordan. (2018) - Wells, Ruth; Lawsin, Catalina; Hunt, Caroline; Said Youssef, Omar; Abujado, Fayzeh; Steel, Zachary
Abstract : Background: There is a need for ecological approaches to guide global mental health programmes that can appropriately address the personal, family, social and cultural needs of displaced populations. A transactional ecological model of adaptation to displacement was developed and applied to the case of Syrian refugees living in Jordan. Methods: Syrian and Jordanian psychosocial workers ( n  = 29) supporting the Syrian refugee community in Jordan were interviewed in three waves (2013–2016). A grounded-theory approach was used to develop a model of key local concepts of distress. Emergent themes were compared with the ecological model, including the five ADAPT pillars identified by Silove (2013). Results: The application of the ecological concept of niche construction demonstrated how the adaptive functions of a culturally significant concept of dignity ( karama ) are moderated by gender and displacement. This transactional concept brought to light the adaptive capacities of many Syrian women while highlighting the ways that stigma may restrict culturally sanctioned opportunities for others, in particular men. By examining responses to potentially traumatic events at the levels of individual, family/peers, society and culture, adaptive responses to environmental change can be included in the formulation of distress. The five ADAPT pillars showed congruence with the psychosocial needs reported in the community. Conclusions: The transactional concepts in this model can help clinicians working with displaced people to consider and formulate a broader range of causal factors than is commonly included in individualistic therapy approaches. Researchers may use this model to develop testable hypotheses.